2014
DOI: 10.1097/wnr.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Smooth pursuit eye movement preferentially facilitates motor-evoked potential elicited by anterior–posterior current in the brain

Abstract: Neural interaction between the eye and hand movement centers must be a critical part of the mechanism underlying eye-hand coordination. One of the previous findings supporting this view is smooth pursuit eye movement-induced suppression of motor-evoked potential (MEP) in the hand muscles. The purpose of this study was to determine which descending volleys contributing to MEP are preferentially modulated by smooth pursuit eye movement. MEP in the first dorsal interosseous muscle was elicited by different direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nevertheless, modulation of saccadic reaction times could also be a result of interactions between saccadic system and smooth pursuit system (e.g., proposed in Tanaka et al, 1998), given the overlap in neural controls for saccades and pursuit (Basso et al, 2000;Krauzlis, 2003Krauzlis, , 2004Orban de Xivry and Lefèvre, 2007). The same is true for manual response, as previous studies revealed close synergies between smooth pursuit and hand movements (Maioli et al, 2007;Hiraoka et al, 2014;Niehorster et al, 2015;Chen et al, 2016aChen et al, , 2016b. Therefore, due to interactions between different motor commands, tasks requiring reaction to probe stimuli are not ideal for investigating attention during smooth pursuit eye movements.…”
Section: Attention Is Allocated Closely Ahead Of the Pursuit Targetmentioning
confidence: 87%
“…Nevertheless, modulation of saccadic reaction times could also be a result of interactions between saccadic system and smooth pursuit system (e.g., proposed in Tanaka et al, 1998), given the overlap in neural controls for saccades and pursuit (Basso et al, 2000;Krauzlis, 2003Krauzlis, , 2004Orban de Xivry and Lefèvre, 2007). The same is true for manual response, as previous studies revealed close synergies between smooth pursuit and hand movements (Maioli et al, 2007;Hiraoka et al, 2014;Niehorster et al, 2015;Chen et al, 2016aChen et al, , 2016b. Therefore, due to interactions between different motor commands, tasks requiring reaction to probe stimuli are not ideal for investigating attention during smooth pursuit eye movements.…”
Section: Attention Is Allocated Closely Ahead Of the Pursuit Targetmentioning
confidence: 87%
“…In contrast, voluntary teeth clenching that involves motor commands from intracortical and thalamocortical sources, in addition to input of sensory feedback via sensorimotor cortex, produces facilitation of PA‐sensitive but inhibition of AP‐sensitive I‐wave inputs for hand muscles (125–127). Furthermore, performing a smooth‐pursuit eye movement task (known to influence excitability in cortical representations for hand muscles) results in specific facilitation of AP‐sensitive inputs to FDI (128), whereas a visual detection task reduces SAI for FDI, but only for AP‐sensitive inputs during high attentional loads (129).…”
Section: Evidence For the Independence Of I‐wave Circuits Activated With Different Current Directionsmentioning
confidence: 99%